2020
DOI: 10.1021/acs.jmedchem.0c00843
|View full text |Cite
|
Sign up to set email alerts
|

Design and Identification of a GPR40 Full Agonist (SCO-267) Possessing a 2-Carbamoylphenyl Piperidine Moiety

Abstract: GPR40/FFAR1 is a G-protein-coupled receptor expressed in pancreatic β-cells and enteroendocrine cells. GPR40 activation stimulates secretions of insulin and incretin, both of which are the pivotal regulators of glycemic control. Therefore, a GPR40 agonist is an attractive target for the treatment of type 2 diabetes mellitus. Using the reported biaryl derivative 1, we shifted the hydrophobic moiety to the terminal aryl ring and replaced the central aryl ring with piperidine, generating 2-(4,4-dimethylpentyl)­ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The plasma concentration of SCO-267 reached more than a few nanograms per milliliter, 24 h after administration of doses $10 mg in the current study. SCO-267 at a dose of 0.3 mg/kg exhibited a C max value of 22.7 ng/mL and was more effective at improving glucose control than the clinically translatable doses of sitagliptin, a dipeptidyl peptidase 4 inhibitor, and fasiglifam in diabetic rats (16,17). In addition, a preclinical study demonstrated that chronic 24-h exposure to SCO-267 was highly effective in improving glycemic control in diabetic rats (19).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The plasma concentration of SCO-267 reached more than a few nanograms per milliliter, 24 h after administration of doses $10 mg in the current study. SCO-267 at a dose of 0.3 mg/kg exhibited a C max value of 22.7 ng/mL and was more effective at improving glucose control than the clinically translatable doses of sitagliptin, a dipeptidyl peptidase 4 inhibitor, and fasiglifam in diabetic rats (16,17). In addition, a preclinical study demonstrated that chronic 24-h exposure to SCO-267 was highly effective in improving glycemic control in diabetic rats (19).…”
Section: Discussionmentioning
confidence: 98%
“…The clinical profiles of full agonists of GPR40 have not yet been evaluated. SCO-267 is an orally available GPR40 full agonist with first-in-class potential for clinical applications (17). SCO-267 has been shown to stimulate the secretion of islet (insulin and glucagon) and gut (glucagon-like peptide 1 [GLP-1], glucose-dependent insulinotropic polypeptide [GIP], and peptide YY [PYY]) hormones in rats (16).…”
mentioning
confidence: 99%
“…Nevertheless, FFA1 receptor modulators still gain a lot of attention from both academic groups as well as the biopharma industry with new chemical matter available and increased understanding of the target biology that led to refined targeting strategiese.g., full ago-PAM versus partial ago-PAM or biased agonists. Further medicinal chemistry efforts have led, for example, to improved FFAR1 agonists with less or no liver toxicity findings in preclinical models [74,75]. Recently, researchers from Janssen Pharmaceutica designed an FFAR1 superagonist that showed higher efficacy on the Gs signaling pathway compared with other full agonists, such as AM 1638, and also a higher potency on both the Gs and Gq pathways [76].…”
Section: Molecular Receptor Pharmacology and Drug Discovery Effortsmentioning
confidence: 99%
“…The follow‐up study indicated that formation of reactive acyl glucuronide was one of the contributors to fasiglifam‐induced liver injury 10 . SCO‐267, the next generation of GPR40 agonist developed by Takeda Pharma, is an orally available GPR40 full agonist that has first‐in‐class potential for the treatment of T2DM 11 . A previous study indicated that SCO‐267 was potent in stimulating insulin secretion and improving glycemic control in diabetic patients with low risk of hypoglycemia 12 .…”
Section: Introductionmentioning
confidence: 99%